1997
DOI: 10.1016/s0009-9236(97)90180-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of valsartan on the angiotensin II pressor response in healthy normotensive male subjects*

Abstract: Valsartan, 80 mg, is a potent angiotensin II antagonist with a rapid onset of action and persistent angiotensin II inhibition up to 24 hours. There is no attenuation of this effect after multiple doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…Results from the two studies showed no change in HR. Complete blockade of pressor effect of Ang II by prior AT 1 antagonism in healthy volunteers has also been reported in other clinical studies done by Shiels et al 17 and Morgan et al 18 Besides the effect on BP, our study also showed that valsartan completely blocked the effect of Ang II on PWV. In the past a study comparing effects of AT 1 receptor blockade (losartan) and ACE inhibition (enalapril) on aortic compliance with similar results, was reported in dogs by Barra et al 19 Multiple linear regression analysis of the data from the present study however suggested that not all of the Ang II induced rise in PWV could be explained by the Ang II induced rise in BP.…”
Section: Discussionsupporting
confidence: 90%
“…Results from the two studies showed no change in HR. Complete blockade of pressor effect of Ang II by prior AT 1 antagonism in healthy volunteers has also been reported in other clinical studies done by Shiels et al 17 and Morgan et al 18 Besides the effect on BP, our study also showed that valsartan completely blocked the effect of Ang II on PWV. In the past a study comparing effects of AT 1 receptor blockade (losartan) and ACE inhibition (enalapril) on aortic compliance with similar results, was reported in dogs by Barra et al 19 Multiple linear regression analysis of the data from the present study however suggested that not all of the Ang II induced rise in PWV could be explained by the Ang II induced rise in BP.…”
Section: Discussionsupporting
confidence: 90%
“…Antagonism of AT1R by various ARBs has also been tested in vivo in humans, mostly healthy volunteers, and, similar to the above animal studies, this was largely done for ANGinduced blood pressure elevations. Following the original study with losartan (Christen et al, 1991), such studies have been performed with candesartan (Delacretaz et al, 1995;Ogihara et al, 1995;Belz et al, 1997Belz et al, , 2000Malerczyk et al, 1998;Fuchs et al, 2000;Gleiter et al, 2004), irbesartan (Belz et al, 1999Maillard et al, 1999;Mazzolai et al, 1999), losartan (Munafo et al, 1992;Belz et al, 1997Belz et al, , 1999Belz et al, , 2000Maillard et al, 1999;Mazzolai et al, 1999;Fuchs et al, 2000;Gleiter et al, 2004), telmisartan Stangier et al, 2001), and valsartan (Müller et al, 1994;Morgan et al, 1997;Belz et al, 1999Belz et al, , 2000Maillard et al, 1999;Mazzolai et al, 1999).…”
Section: Antagonism In Vivomentioning
confidence: 99%
“…To prevent any further confounding interference resulting potentially from the effect of an acute AT1R blockade on endogenous AngII (Gandhi et al, 1996;Burnier et al, 1996;Schmitt et al, 1998), a short-term, high-dose VAL pretreatment timed to provide the last dose in the evening before AngII infusion was preferred instead of administering an ARB single dose close to the beginning of AngII infusion. An effective AT1R blockade was assumed to be maintained in the morning after the last VAL administration on the basis of previous data indicating that the pressor effect of exogenous AngII was blunted even 12 h after a single dose of 80 to 160 mg of VAL (Morgan et al, 1997;Latif et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Because ARBs are known to counteract effectively any action of exogenous AngII on systemic vasculature, adrenal tissues, and kidney (Gandhi et al, 1996;Morgan et al, 1997;Schmitt et al, 1998), low-dose AngII infusion may be a suitable experimental condition for determining the role of BK in both the renal actions of AngII in humans and their inhibition exerted by AT1R blockade. The purpose of the present work was to investigate whether BKB2R blockade affects BP and renal changes during AngII infusion in salt-repleted, healthy humans with and without a previous short-term AT1R blockade.…”
Section: Introductionmentioning
confidence: 99%